Asciminib vs bosutinib in CML patients pretreated with ≥2 tyrosine kinase inhibitors: Results from the Japanese subgroup analysis of ASCEMBL study. (27th September 2022) - Yuda, Junichiro; Doki, Noriko; Matsuoka, Hiroshi; Yokota, Takafumi; Tomita, Akihiro; Takahashi, Naoto; Matsumura, Itaru; Kubo, Kohmei; Goto, Tatsunori; Kirito, Keita; Maki, Akio; Aoki, Makoto; et al.
Abstract: Asciminib, a first‐in‐class, allosteric inhibitor of BCR‐ABL1 that acts by STAMP (Specifically Targeting the ABL Myristoyl Pocket), is a novel therapeutic option for patients with chronic myeloid leukemia (CML). In the global, phase 3, open‐label ASCEMBL study in patients with CML in chronic phase (CML‐CP) pretreated with ≥2 tyrosine kinase inhibitors (TKIs) (NCT03106779), asciminib (40 mg twice‐daily) demonstrated significant superiority over the ATP‐competitive TKI bosutinib (500 mg once daily) for the primary endpoint of major molecular response (MMR; BCR::ABL1 transcript levels on the international scale [ BCR::ABL1 IS ] ≤0.1%) at week 24. Here, we report results from a descriptive subgroup analysis of Japanese patients enrolled in ASCEMBL study (data cut‐off: May 25, 2020). Overall, 16 Japanese patients were randomized (asciminib, n  = 13; bosutinib, n  = 3). At week 24, the MMR rate with asciminib was 30.8% (4/13; 95% confidence interval [CI], 9.09–61.43). BCR::ABL1 IS ≤1% and complete cytogenic response (CCyR) at week 24 were 61.5% (8/13 patients) and 50.0% (4/8 patients), respectively. In the bosutinib group, no patient achieved MMR, CCyR, or BCR::ABL1 IS ≤1%, but results were limited by the low number of patients. The safety profile of asciminib was comparable to that previously observed in the overall study population. Findings from this Japanese subgroup analysis of the ASCEMBL study support the use of asciminib for the treatment of Japanese patients with CML‐CP previously treated with ≥2 TKIs. ClinicalTrials.gov Identifier: NCT03106779. Abstract : Asciminib, a first‐in‐class, allosteric inhibitor of BCR‐ABL1 that acts by STAMP (Specifically Targeting the ABL Myristoyl Pocket), is a novel therapeutic option for patients with chronic myeloid leukemia (CML). In the global, phase 3, open‐label ASCEMBL study in patients with CML in chronic phase (CML‐CP) pretreated with = 2 tyrosine kinase inhibitors (TKIs), asciminib (40 mg twice‐daily) demonstrated statistically significant superiority over the ATP‐competitive TKI bosutinib (500 mg once daily) for the primary endpoint of major molecular response (MMR; BCR‐ABL1 transcript levels on the international scale [BCR‐ABL1IS] = 0.1%) at week 24. Here, we present a descriptive subgroup analysis results of Japanese patients enrolled in the ASCEMBL study.